What Is Educational about Education? The Distinctiveness of Education. Issue 1 (21st July 2021) - Norris, Trevor
Abstract: This article explores two questions: (1) Is education a unique and distinct discipline? (2) Is education anything other than the achievement of noneducational aims or objectives? In it, Trevor Norris examines how these two questions are interconnected, specifically analyzing how what we think about education as a distinct field of study informs what we ask of it as a practice. When we study education, we should be educational about it, because if we render education as the object of study, it is never endowed with agency or distinctiveness. Norris inquires into the distinctiveness of education as a way of thinking and a way of impacting the world, asking what are the conditions that make it possible for us to identify something as "educational"? To investigate this question, Norris draws from Hannah Arendt's account of politics, and he concludes by describing a case study assignment that requires educational foundations students to draw from philosophy of education in order to show what exactly is educational about education by contrasting education with business and psychology.